Gut colonization of Bacteroides plebeius suppresses colitis-associated colon cancer development - Hung-Lin Chen; Po-Yuan Hu; Chang-Shan Chen; Wei-Han Lin; Daniel K. Hsu; Fu-Tong Liu; Tzu-Ching Meng (Microbiology Spectrum)
ABSTRACT Colon cancer development may be initiated by multiple factors, including chronic inflammation, genetic disposition, and gut dysbiosis. The loss of beneficial bacteria and increased abundance of detrimental microbes exacerbates disease progression. Bacteroides plebeius (B. plebeius) is a human gut microbe, and its colon colonization is enhanced by a seaweed-supplemented diet. We found that mice orally administered with B. plebeius and fed a diet containing 1% seaweed developed a unique gut microbial composition. By linear discriminant analysis effect size analysis, we found that B. plebeius colonization increased the abundance of Blautia coccoides and reduced the abundance of Akkermansia sp. and Dubosiella sp. We also showed that colonization of B. plebeius suppressed the colon tumor development induced by azoxymethane/dextran sulfate sodium in specific-pathogen-free mice, coinciding with a reduced abundance of Muribaculaceae sp., Closteridale sp., and Bilophila sp. Moreover, B. plebeius colonization in gnotobiotic mice resulted in enhanced production of selected metabolites, including propionic, taurocholic, cholic, alpha-, and beta-muricholic, as well as ursodeoxycholic acids. Importantly, some of these metabolites show anti-inflammatory and tumor-suppressive effects. We conclude that B. plebeius is able to restructure the gut microbial community and produce beneficial metabolites, leading to inhibition of colitis-associated colon cancer development.IMPORTANCEThis work delves into the pivotal role of gut microbiota in suppressing the progression of colitis-associated colon cancer. By investigating the impact of Bacteroides plebeius that can be colonized in mouse gut by feeding the animal with seaweed diet, we unveil a novel mechanism through which this beneficial bacterium reshapes the gut microbial community and produces metabolites with anti-inflammatory and tumor-suppressive properties. Such findings underscore the potential of harnessing specific microbes, like B. plebeius shown in this study, to modulate the gut ecosystem and mitigate the risk of colitis-associated colon cancer.